Pengembangan Karakter Religius Melalui Ekstrakurikuler di MAN 2 Kebumen - latifah, Nurul; Chamidi, Agus Salim (Tarbi: Jurnal Ilmiah Mahasiswa, 2025)
Education that only prioritizes intellectual intelligence is apparently not enough as a provision in life. Because the noble ideals of the Indonesian people are not only to have intellectual intelligence, but also to become a nation that has noble character accompanied by religious character values. Actually, moral education has now been implemented in education, especially in Islamic Religious Education (PAI). However, the actualization of morals or morals taught in schools has not been able to overcome the current moral problems, such as juvenile delinquency. Religious character development can be done in various ways, one of which is through extracurricular activities. Based on that, researchers conducted research at MAN 2 Kebumen with the title Religious Character Development Through Extracurriculars at MAN 2 Kebumen. This study aims to describe the development of students' religious character as well as the supporting and inhibiting factors in the development of religious character through extracurricular activities at MAN 2 Kebumen. This study uses a type of qualitative research approach. Collecting data using interview techniques, observation and documentation. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of this study indicate that the IRMAS extracurricular at MAN 2 Kebumen can have a positive impact on students who take part in the extracurricular and inculcate religious character values. This can be seen from daily life at the madrasa such as behavior, morals, discipline in worship, complete attributes of its members.